2016
DOI: 10.4172/2161-0959.1000246
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Health-Related Quality of Life in Patients Receiving Regular Hemodialysis

Abstract: ResultsAmong the 81 HD patients studied (49 males + 32 females) aged 50.6 ± 12.7 years, HRQOL scores were poor in all domains and subscales. The mean total score was 47.2 ± 25.2, mean Physical Health Composite (PHC) = 35.57 ± 7.34 and mean Mental Health Composite AbstractThis cross-sectional descriptive study was carried out at the hemodialysis unit of Karmouz Health Insurance Hospital, Alexandria, Egypt. The study was conducted on adult End-stage renal disease (ESRD) patients maintained on regular hemodialysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
(32 reference statements)
1
7
0
Order By: Relevance
“…The findings are consistent with the study conducted by Abdelghany et.al., found that the mean total score was below 50 (out of 100 point) with mean PH composite (PHC)=35.57±7.34 and mean mental health composite=36.76±10.22 which revealed that all domains of HRQOL were reduced and very poor in HD patients. Anemia and unemployment adversely affected HRQOL scores [25]. The result of the study findings is parallel with the study conducted by Sathvik et.al.…”
Section: Discussionsupporting
confidence: 89%
“…The findings are consistent with the study conducted by Abdelghany et.al., found that the mean total score was below 50 (out of 100 point) with mean PH composite (PHC)=35.57±7.34 and mean mental health composite=36.76±10.22 which revealed that all domains of HRQOL were reduced and very poor in HD patients. Anemia and unemployment adversely affected HRQOL scores [25]. The result of the study findings is parallel with the study conducted by Sathvik et.al.…”
Section: Discussionsupporting
confidence: 89%
“…33 Variables Β 95% CI Further, we noted a significant relationship between employment and QoL and our findings further support findings from other studies. 33,34 Employment is reported to improve QoL of ESRD patients probably due to the regular income which caters for the costs of treatment. 33,34 There are limitations in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Employment is reported to improve QoL of ESRD patients probably due to the regular income which caters for the costs of treatment. 33,34 There are limitations in the present study. Some of the patients were interviewed during dialysis; therefore, immediate effects of dialysis on symptom reporting such as hypotension cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…However, marital status has been the focus of several studies. On the one hand, there is a belief that family is a social support network (19), while, on the other hand, researchers argue that family obligations increase family anxiety, resulting in negative QoL (13).…”
Section: Discussionmentioning
confidence: 99%